Application of comprehensive pharmaceutical care program in identifying and addressing drug-related problems in hospitalized patients with osteoporosis - Wenwen Chen; Houli Zhang; Juan Jiang; Xu Zhang; Jing Ding; Yanlin Liu; Heqin Dang (BMC, 2022)
Abstract Background More information about the impacts of comprehensive pharmaceutical care program (CPCP) on the identification and resolution of drug-related problems (DRPs) is needed. This study aimed at researching the characteristics of DRPs in osteoporosis patients and evaluating the effect of CPCP in identifying and addressing DRPs. Methods We performed a prospective interventional study in a teaching hospital. CPCP was established and conducted to identify and resolve DRPs by a multidisciplinary team (MDT) based on the Pharmaceutical Care Network Europe (PCNE) classification V9.0. Six pharmacists and one doctor worked directly in the study. All data was obtained from electronic medical records, direct observation and visits. The statistical analyses were performed using the SPSS Statistics software version 26.0. Results Two hundred nineteen patients with osteoporosis were included in the final analysis. A total of 343 DRPs were identified, with an average of 1.57 DRPs per patient. The most common DRPs identified were "treatment safety P2" (66.8%; 229/343), followed by "other P3" (21.0%; 72/343) and "treatment effectiveness, P1" (12.2%; 42/343). The primary causes of DRPs were "dose selection C3" (35.9%; 211/588), followed by "drug use process C6" (28.9%; 170/588) and "drug selection C1" (12.6%; 74/588). Seven hundred eleven interventions were proposed to address the 343 DRPs, with an average of 2.1 interventions per DRP. The acceptance rate reached 95.9, and 91.0% of these accepted interventions were fully implemented. As a result, only 30 DRPs were unsolved before discharge. Additionally, the number of drugs was found to be associated with the number of DRPs significantly (p = 0.023). Conclusion DRPs frequently occurred in hospitalized osteoporosis patients. CPCP could be an effect option to solve and reduce DRPs for osteoporosis patients and should be implemented widely to increase patient safety.